Adult-onset Still's disease with myocarditis and hemophagocytic lymphohistiocytosis: Rare manifestation with fatal outcome - Devika Gupta; Rajat Jagani; Satish Mendonca; Khushi Ram Rathi (Wolters Kluwer Medknow Publications, 2016)
Adult-onset Still's disease (AOSD) is a rare inflammatory disorder of unknown etiology characterized by fever, evanescent pink salmon rash, arthritis, and multiorgan involvement. Here, we report an unusual manifestation of AOSD in a 40-year-old male who presented to our hospital with pyrexia of unknown origin and rash of 3 weeks duration. All his serological investigations and imaging studies were unremarkable. He was fulfilling clinical and laboratory criteria as per Yamaguchi for AOSD and was managed for the same. Our patient did not respond well to the treatment, had a downhill course, and succumbed to his illness. Autopsy confirmed myocarditis and florid bone marrow reactive hemophagocytosis as the cause of his death.